A co-expression strategy to achieve labeling of individual subunits within a dimeric protein for single molecule analysis. Issue 57 (26th June 2017) - Lou, Fei; Yang, Jie; Wu, Si; Perrett, Sarah
Abstract : Site-specific incorporation of donor–acceptor pair into a dimeric protein for single-molecule FRET analysis is realized based on a co-expression strategy. Abstract : A generic co-expression strategy for site-specific incorporation of a single donor–acceptor dye pair into any position in a dimeric protein, allowing single molecule FRET study of proteins previously inaccessible to this technique, such as the intrinsically disordered prion N-domain of Ure2 in the context of its globular dimeric C-domain.